Political Erosion in 'The Land of Steady Habits': Party Politics in Connecticut's 2018 Gubernatorial Election - Wharton, Jonathan L. (New England Journal of Political Science, 2019)
Keywords: dept.psc; peer-reviewed; ⛔ No DOI found

Populism and British stories of decline - Murphy, Joshua (American Journal of Economics and Sociology, 2019)
The British Empire reached its territorial peak less than a century ago in 1920 when one could walk from South Africa to Kuwait and not set foot in a country in which English was not the language of government. By 1959, India, Australia, New Zealand, South Africa, Egypt, Sudan, and other countries were no longer within Britain's imperial fold. In the space of little more than 30 years, the British Empire suffered a precipitous decline and collapse that left the United Kingdom of Great Britain and Northern Ireland little more than the rump successor state of a once great empire. Yet, imperial attitudes lingered and have an undue influence on British life, culture, and politics up to the present day. Through the lens of pivotal moments in the world since World War II, this article examines the breakup of the British Empire and how the vision of empire lives on in the context of global populism.
0 citations (Crossref) [2023-10-31] tex.eissn: 1536-7150 tex.unique-id: ISI:000468313600008
Keywords: dept.psc; peer-reviewed

Male versus female career ambassadors: is the US Foreign Service still biased? - Calin, Costel; Buterbaugh, Kevin (Foreign Policy Analysis, 2019)
This paper examines the appointment of male versus female career diplomats to ambassadorial posts. We assess the role played by ambassadors' individual characteristics, including education, marital status, and number of children, and host countries' characteristics, such as quality of life and regime type, in determining if a male or female is appointed to ambassadorial positions to represent the United States in foreign countries. The time frame of this study is the entire presidencies of Bill Clinton and George W. Bush (1993-2008), during which 603 career diplomats were appointed as ambassadors. The study provides empirical evidence that there remain significant differences between women and men serving as ambassadors. Female ambassadors are more likely to be single and have no children and are less likely to be Ivy League graduates than male ambassadors. Furthermore, they are more likely to be appointed to countries with lower quality of life and better human rights records. Finally, time plays a role in the likelihood of a woman being appointed as ambassador.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000481423500004, lens.org/085-024-674-912-250 tex.address: [object Object] tex.affiliation: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: dept.psc; peer-reviewed

Book Review: Farnsworth, Stephen J. 'Presidential communication and character: White House news management from Clinton and cable to twitter and Trump' - Hopper, Jennifer (Congress & the Presidency, 2019)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-328-675-126-964
Keywords: book.review; dept.psc